2021
DOI: 10.1093/ejcts/ezab216
|View full text |Cite
|
Sign up to set email alerts
|

Five-year outcome in 18 010 patients from the German Aortic Valve Registry 

Abstract: OBJECTIVES To determine the 5-year outcome in patients treated by isolated transcatheter aortic valve implantation (TAVI) or surgical aortic valve replacement (sAVR)—a prospective observational cohort study. METHODS A total of 18 010 patients were included (n = 8942 TAVI and n = 9068 sAVR) in the German Aortic Valve Registry (GARY) who were treated in 2011 and 2012 at 92 sites in central Germany. Eligible patients with TAVI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 16 publications
3
27
0
1
Order By: Relevance
“…On the other hand, the most recent real-world analysis of the GARY registry, published by Beyersdorf et al, in 2021, showed a difference in the 5-year outcomes. The study, conducted on a propensity score-matched collective chosen from a total of 18010 patients (1820 TAVR vs. 1820 iSAVR), showed a significantly reduced long-term survival (hazard ratio 1.51, 95% confidence interval 1.35–1.68; p < 0.0001) after an implantation of early generation TAVI valves compared with SAVR [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the most recent real-world analysis of the GARY registry, published by Beyersdorf et al, in 2021, showed a difference in the 5-year outcomes. The study, conducted on a propensity score-matched collective chosen from a total of 18010 patients (1820 TAVR vs. 1820 iSAVR), showed a significantly reduced long-term survival (hazard ratio 1.51, 95% confidence interval 1.35–1.68; p < 0.0001) after an implantation of early generation TAVI valves compared with SAVR [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…While durability is no explanation for the mortality differences 37 most prominently observed in propensity-matched registry analyses, 38 the combination of other adverse events may be plausible. Several registries illustrated that mild paravalvular leaks (more frequent in TAVI) may already be prognostically relevant.…”
Section: Surgical Treatment Of Valve Diseasementioning
confidence: 99%
“…Fig.5(A) Survival after TAVI or SAVR in propensity-matched patients from the Germany Aortic valve Registry (GARY) (Reproduced with permission of Beyersdorf et al 202138 ). (B) Landmark analysis from a reconstructed individual patient-data meta-analysis having included all randomized trials with 5-year follow-up comparing SAVR and TAVI (Reproduced with permission of Doenst et al 202134 ).…”
mentioning
confidence: 99%
“…Surgical aortic valve replacement (SAVR) has always been the optimal treatment for patients with AS across different risk stratifications (5,6). However, several important clinical studies regarding transcatheter aortic valve replacement (TAVR) (7)(8)(9)(10) have demonstrated the efficacy and safety of TAVR all over the world (11,12). It is estimated that more than 306,000 patients with AS have undergone TAVR in the United States (13).…”
Section: Introductionmentioning
confidence: 99%